PODCAST AS A PEDAGOGICAL TOOL FOR TEACHING SPANISH WITHIN THE CONTEXT OF EPT (INSTITUTO FEDERAL FLUMINENSE) (Interdisciplinary Studies Journal, 2024)
This article presents the results of a qualitative study conducted at the Language Center of the Instituto Federal Fluminense, Campos Centro campus, aimed at evaluating the effectiveness of a didactic sequence based on the use of podcasts for teaching the Spanish language. Developed within the context of the Postgraduate Program in Professional and Technological Education (ProfEPT). Methodologically, it is a qualitative approach study, with descriptive-exploratory objectives, applied nature, and supported by two methodological procedures: bibliographic research and action research. The data collection instruments included interviews and online questionnaires (SurveyMonkey). The research population consisted of six students enrolled in Level 1 of the Spanish course, as well as the Spanish teacher and the coordinator of the courses offered by the center. The didactic sequence was designed to explore the use of podcasts as a pedagogical tool, aiming for more flexible teaching adapted to the individual needs of students, in addition to the textbook. As the main result, there was progress in the field of language education by demonstrating the feasibility and benefits of integrating digital media, specifically podcasts, as pedagogical tools in foreign language teaching, paving the way for future research and new practices in this field.
Keywords: Professional and Technological Education; Teaching of Spanish Language; Didactic Sequence; Podcast